Perancangan Video Promosi Berbasis Motion Graphic Pada Catering Salsabila Ungaran - Firda Vera Salsabila; Agus Priyadi; Ahmad Zainudin (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
Audiovisual media is a key promotional tool for enhancing a business’s brand. This study aims to design a motion-graphic-based promotional video for Salsabila Catering in Ungaran as a branding strategy to increase sales and raise public interest in their products. The research method employed is research and development using the multimedia development life cycle approach. The results indicate that the promotional video produced is deemed visually and substantively suitable; as validated by both experts based on the assessment percentages obtained. According to the expert validation presentation; the content received a 77% rating; deemed acceptable; while the media expert test yielded an 83% result; deemed highly acceptable. Additionally; audience evaluations resulted in an 87% rating; categorized as “very good” and “highly satisfied” regarding the content; presentation; and message conveyed in the promotional media.